Differences in Motor Development between Preterm Infants and Full-Term Preschool Children - Alicia Cuesta-Gómez; Pilar Fernández-González; María Carratalá-Tejada; Inmaculada Aguilar-Bejines (MDPI AG, 2024)
Although advances in obstetric and neonatal care have improved the survival of preterm infants, many studies document the increased risk of motor and sensory neurodevelopmental abnormalities that can hinder school progress. The aim of this study was to analyze the differences in gross and fine motor development in children born preterm and full term aged 3 to 6 years using the Peabody Developmental Motor Scales 2 (PDMS-II). Fifteen preterm and fifteen term children, matched for age and sex, participated in this study. They were evaluated with the PDMS-II scale. The scores obtained in the PDMS-II scale showed statistically significant differences (p < 0.05) in all subscales except for the "grasping" subscale. No dissimilarities were found between children who attended an early intervention program and those who did not participate, nor was there any correlation between week of gestation and birth weight and motor development in preschool. The results obtained show that differences are found with respect to motor development, with lower scores for those born preterm compared to children born at term. No statistically significant difference was found between preterm children who attended early intervention and those who did not. No correlation was found between motor development at preschool age and birth weight and gestational age.